Rancang Bangun Sistem Informasi Penjualan Perlengkapan Futsal Berbasis Web - hendro Priyono (Universitas Bina Sarana Informatika, 2019)
In the current global era, the internet is one technology that provides information for all parties through various existing websites. In foreign countries, the internet in general can hardly be separated from the world of education. While in Indonesia internet use can be connected to all types of fields. Both education, entertainment, moreover the world of business (e-commerce). For that in scientific writing, the author makes a website that can provide information to the public related to the world of business (e-commerce), namely Website Creation Selling Futsal Equipment Using Adobe Dreamweaver CS5 and using MySQL as its database, which is expected to benefit all the wider community. In addition, the most famous information access system on the internet is the World Wide Web (WWW) or commonly known as We have grown so rapidly that it can exceed the speed of other technological developments in this world. The Internet and the Web are also growing rapidly in terms of the extent and breadth of fields of use that significantly affect several aspects of life. All areas of life also feel the impact of the developments that occur. Industry, travel agencies, hospitals, banking, education and government use the Web to improve operational efficiency in carrying out its functions. The use of the internet can now be found in almost every layer.Keywords: Website, Selling Futsal Equipment, PHP, Dreamweaver CS5